Bilateral Trevor’s disease of the posterior talus - Katherine van Kampen; Karim Gaber; Zachary Lupson; Waleed Kishta (Journal of Orthopaedic Reports, 2024)
Background: Dysplasia eiphysealis hemmimelica also known as Trevor's disease is a rare disorder in which there is overgrowth of the epiphyses. It often presents as a painless mass around the affected joint that increases in size. It is commonly found in children and treated with excision if operative treatment is elected. Case report: We present a case of a thirteen-year-old male complaining of nontraumatic right ankle pain and bony growth. Upon further work up, the patient was diagnosed with Trevor's Disease in the os trigonum. This case study reviews the clinical symptoms, diagnosis and treatment of the disease. Notably, the patient presented was treated with a unique multimodal method including operation and injection of bone marrow. More unusual was that the lesion was bilateral and found contralaterally 3 years later. Conclusion: This case is unique in its presentation and management as well as unlikely occurrence bilaterally three years later.